2012
DOI: 10.1097/dad.0b013e318234cc49
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Periodic Acid–Schiff Stains of Nail Clippings as a Second-Line Diagnostic Tool in Onychomycosis

Abstract: The diagnosis of onychomycosis, using direct microscopy and fungal cultures, is often negative despite the presence of disease. Periodic acid-Schiff (PAS) staining of nail clippings, using histopathological processing, may be positive in these cases. It is not always clear, however, whether the fungal elements detected by PAS staining are pathogenic fungi or some are saprophytes. We aimed to study the efficacy of histopathological PAS staining of nail clippings as a second-line diagnostic tool in onychomycosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 10 publications
0
12
0
2
Order By: Relevance
“…Mayer et al . in their study included 100 consecutive cases in which direct microscopy and fungal cultures from suspected onychomycosis were negative on one occasion or more. They concluded that as a second‐line diagnostic tool, PAS stain of nail clippings increases markedly the diagnostic yield of onychomycosis over and above direct microscopy and culture.…”
Section: Discussionmentioning
confidence: 99%
“…Mayer et al . in their study included 100 consecutive cases in which direct microscopy and fungal cultures from suspected onychomycosis were negative on one occasion or more. They concluded that as a second‐line diagnostic tool, PAS stain of nail clippings increases markedly the diagnostic yield of onychomycosis over and above direct microscopy and culture.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of nail clipping studies fix the specimens in formalin [18, 10,17], some apply substances for softening of the nail plate, like chitin-softening solution [1,10] and Tween solution [5]. Several articles mentioned using traditional routine histologic examination for nail processing [1,2,3,7,10], few studies applied what seemed to be a diverse microscopic processing only with a series of ethanol [4,6], and a few did not use any microscopic processing at all after fixing with formalin and before paraffin embedding [5,8]. One study obtained good histologic preparations without using a fixative and immersed nail fragments in a solution of liquid hand soap and distilled water followed by a process in a routine overnight cycle [16], and in only two reports the samples examined were immediately wrapped in paraffin without using a fixative liquid [9,17].…”
Section: Discussionmentioning
confidence: 99%
“…Nail plate microscopic analysis in PAS stained slides, also known simply as nail clipping, is an established test used in the diagnosis of onychomycosis [17], and in one study it proved to have a role in discovering clinically unapparent nail fungal infection [8]. Its application in evaluating causes of onychodystrophy other than fungal infection is reported to a very small extent, though [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Aslında onikomikoz tanısı için klinik şüphe yanında en az bir laboratuvar testinin pozitif olması önerilir 2 . Klasik olarak tanıda, direkt mikroskopik inceleme ve kültür tanı yöntemleri kullanılırken son yıllarda histopatolojik inceleme tamamlayıcı bir yöntem olarak yerini almıştır 3,4 . Bunların dışında immunfloresan boyamalar, in vivo konfokal mikroskopi, polimeraz zincir reaksiyonu (PCR) gibi moleküler teknikler ve enzim analiz yöntemleri tanı için kullanılmaktadır [5][6][7] .…”
Section: Introductionunclassified
“…Bunların dışında immunfloresan boyamalar, in vivo konfokal mikroskopi, polimeraz zincir reaksiyonu (PCR) gibi moleküler teknikler ve enzim analiz yöntemleri tanı için kullanılmaktadır [5][6][7] . Onikomikozda tanı yöntemlerinin etkinliğini değerlendiren çeşitli çalışmalar mevcuttur 2,4,[8][9][10][11][12][13][14][15][16] . Altın standart olarak değerlendirilen tanı yöntemi, çalışmalarda farklılık göstermektedir.…”
Section: Introductionunclassified